The importance of crowd support and team quality to home advantage in Brazilian Soccer League first division - Dellagrana, R. A.; Nunes, R. F. H.; Silva, R. L. P. (Perceptual and Motor Skills, 2023)
Our aims in the present study were to analyze home advantage (HA) and number of goals scored in consideration of the presence or absence of crowd support and the influence of team quality during the last 11 seasons of the Brazilian Soccer League first division. We analyzed data from 4162 matches played in the Brazilian Soccer League in seasons 2012-2022 (3563 matches with an audience and 599 matches without an audience). We calculated HA by comparing the number of points won at home as a percentage of the total number of points gained, and we also recorded the number of goals scored by home and away teams. For analyses, we divided the teams based on home and away matches, with and without crowds, and we classified teams into three ability groups, based on the points scoring percentage of the team at the end of the season. There was a HA in all seasons analyzed (i.e., home teams won more than 50% of the total points won at home); but in matches in empty stadiums, the HA was reduced significantly, compared to matches with crowd support (66.6% with crowd vs. 57.2% without crowd, p < 0.05). The number of goals in all seasons was higher for home teams than for away teams; however, away teams scored more goals in empty stadiums than in stadiums with crowd support (p < 0.05). The HA was greater in matches with crowd support than in matches without crowd support (p < 0.01), independent of the team`s ability level; but, top teams scored more goals than weaker teams (p < 0.01). In conclusion, in the Brazilian Soccer League, the HA and number of goals scored were affected by the presence or absent of an audience in the stadiums. While top teams scored more goals than weaker teams, the HA was lower without than with crowds, independent of team quality.